2018
DOI: 10.1063/1.5048595
|View full text |Cite
|
Sign up to set email alerts
|

Riddling: Chimera’s dilemma

Abstract: We investigate the basin of attraction properties and its boundaries for chimera states in a circulant network of Hénon maps. It is known that coexisting basins of attraction lead to a hysteretic behaviour in the diagrams of the density of states as a function of a varying parameter. Chimera states, for which coherent and incoherent domains occur simultaneously, emerge as a consequence of the coexistence of basin of attractions for each state. Consequently, the distribution of chimera states can remain invaria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In qualitative terms, the fractals generated by our network of coupled quadratic maps seem less filigree, more disordered, but even fuller of variety than the Mandelbrot set. Complementing previous work [21][22][23] , our study establishes an intriguing link between the dynamics of partially synchronized networks and the geometry of fractals in the complex plane.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…In qualitative terms, the fractals generated by our network of coupled quadratic maps seem less filigree, more disordered, but even fuller of variety than the Mandelbrot set. Complementing previous work [21][22][23] , our study establishes an intriguing link between the dynamics of partially synchronized networks and the geometry of fractals in the complex plane.…”
supporting
confidence: 71%
“…21-23. These studies showed that the set of initial conditions leading to chimeras 21,22 or sub-chimeras 23 form riddled and fractal basins of attraction for networks of Rössler dynamics 22 , Henon maps 21 , logistic maps 23 , and sine-squared maps 23 (see also Ref. 56).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations